Population density and reproduction of two Peruvian leaf-eared mice (Phyllotis spp.) Densidad poblacional y reproducción de dos ratones orejudos del Perú (Phyllotis spp.) - MARGARITA ARANA (Revista Chilena de Historia Natural, 2002)
Population density and reproduction were studied in two leaf-eared mice (Phyllotis spp.) in the Peruvian locality known as Lomas de Lachay. Density varied between 0-3 individuals ha-1 in P. andium, and between 0-12 individuals ha-1 in P. amicus. An annual cycle of population abundance was observed in both species. Phyllotis amicus showed no seasonal reproductive activity, but P. andium had seasonal reproduction with pregnant females principally observed between July and September. Differences in juvenile weight were related to litter size. It is likely that two young was the optimal litter size in the harsh and seasonal xeric environment of Lomas de Lachay. Our results suggest that P. amicus maintains low, highly dispersed populations in a harsh environment, and can reproduce at any time of the year, whereas P. andium appears to be a more irruptive species closely tied to rainfall patterns La densidad poblacional y reproducción de dos ratones orejudos (Phyllotis spp.) fueron estudiadas en la localidad peruana Lomas de Lachay. La densidad varió entre 0-3 individuos ha-1 en P. andium, y entre 0-12 individuos ha-1 en P. amicus. En ambas especies se observaron cambios poblacionales que sugieren la existencia de ciclos anuales en la abundancia poblacional. El patrón reproductivo en las dos especies de Phyllotis fue claramente distinto. Phyllotis amicus mostró una actividad reproductiva no estacional, mientras que P. andium tuvo una reproducción estacional observándose hembras preñadas principalmente entre julio y septiembre. La diferencia en el peso de los juveniles estuvo relacionada con el tamaño de la camada. Es probable que en las Lomas de Lachay el tamaño de camada óptimo sea de dos individuos. Nuestros resultados sugieren que P. amicus es una especie que mantiene poblaciones bajas, altamente dispersas en áreas desérticas, y que puede reproducirse durante todo el año; mientras que P. andium parece ser una especie que irrumpe más en ambientes arbustivos dependientes de patrones de precipitación pluvial